Interior of the Mukhamandapa (front porch) - Temples of India Project Team (Jio Institute, 2024)
The mukhamandapa (front porch) is an open hall with a magnificent entrance dominated by a makara-torana (ornamental arch adorned with intricate carvings of mythical crocodile creatures). The pillars of the mukhamandapa are carved with the figures of sursundaris (celestial maidens) and passionate couples, symbolizing the worldly realm. This stands in contrast to the main sanctum where the divine resides in darkness.